2008
DOI: 10.1080/09500340701847895
|View full text |Cite
|
Sign up to set email alerts
|

Optical interferometry with pulsed fields

Abstract: The problem of predicting and interpreting the results of interferometric optical experiments involving pulse trains is addressed. Specifically, a cyclostationary field arising from the modulation of a stationary, stochastic source is considered in the classical Young's experiment. It is shown that the effects of modulation may be identical to unrelated statistical interference effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The interferogram produced in such an experiment also can be used to determine the approximate coherence time (and thus the bandwidth) of the impinging field. For cyclostationary plane waves, it has been shown that in a Young's interferometer the meaning of the interferogram is changed and there is some ambiguity in connecting the results to the source parameters [7]. Specifically, it was shown that the smaller of the pulse duration, T, and the coherence time, c , sets the width of the primary peak in the interferograms.…”
Section: ͑13͒mentioning
confidence: 99%
See 4 more Smart Citations
“…The interferogram produced in such an experiment also can be used to determine the approximate coherence time (and thus the bandwidth) of the impinging field. For cyclostationary plane waves, it has been shown that in a Young's interferometer the meaning of the interferogram is changed and there is some ambiguity in connecting the results to the source parameters [7]. Specifically, it was shown that the smaller of the pulse duration, T, and the coherence time, c , sets the width of the primary peak in the interferograms.…”
Section: ͑13͒mentioning
confidence: 99%
“…In works on nonstationary fields [6,7,20], the emphasis has been on sources that are spatially fully coherent and of infinite extent. Such sources produce polychromatic plane waves.…”
Section: Propagation Of Correlations and Interferometrymentioning
confidence: 99%
See 3 more Smart Citations